Humidification mitigates acute mucosal toxicity during radiotherapy when factoring volumetric parameters. Trans Tasman Radiation Oncology Group (TROG) RadioHUM 07.03 substudy. (December 2017) - Macann, A.; Fauzi, F.; Simpson, J.; Sasso, G.; Krawitz, H.; Fraser-Browne, C.; Manitz, J.; Raith, A.
Highlights: Humidification ameliorates mucositis symptoms by limiting dessication injury. The degree of humidifcation compliance correlates with benefit. Future research needs to focus on improving humidifcation compliance. Radiotherapy dosimetric parameters assist in evaluating toxicity interventions. Abstract: Purpose/Objective(s): To model in a subset of patients from TROG 07.03 managed at a single site the association between domiciliary based humidification use and mucositis symptom burden during radiotherapy (RT) for head and neck cancer (HNC) when factoring in volumetric radiotherapy parameters derived from tumour and normal tissue regions of interest. Materials/Methods: From June 2008 through June 2011, 210 patients with HNC receiving RT were randomised to either a control arm or humidification using the Fisher & Paykel Healthcare MR880 humidifier. This subset analysis involves patients recruited from Auckland City Hospital treated with a prescribed dose of ≥70 Gy. Regression models included control variables for Planning Target Volume 70 GY (PTV70Gy); Equivalent Uniform Dose (EUD) MOIST and TSV (surrogates of total mucosal and total swallowing volumes respectively). Results: The analysis included 39 patients (humidification 20, control 19). There was a significant odds reduction in CTCAE v3.0 functional mucositis score of 0.29 associated with the use of humidification (p < .001). Within the parameters of the model therefore, the risk of a humidification patient being scored as experiencing a one-step increase in functional mucositis was 3.45 times lower (1/0.29) than for control patients. A control patient was 4.17 times more likely to receive an unfavourable nutritional mode score (p < .001). The risk of being admitted to hospital decreased by a factor of 11.11 for humidification patients (p = .013). Conclusion: The results support the hypothesis that humidification can help mitigate mucositis symptom burden. Radiotherapy dosimetric parameters assist in the evaluation of toxicity interventions.